BIOGRAPHICAL APPROACH TO THE INTERPRETATION OF HUMAN QUALITIES IN A. NAVOI’S EPIC “LAYLI AND MAJNUN” - Adizova, Obodon Ismatovna; Toirova, Mavluda Hamidovna; Ramazonova, Zarina Gafurovna (International Journal of Psychosocial Rehabilitation, 2020)
almost every Persian, Arabic, and Turkish ghazal of Alisher Navoi, from the epics of “Khamsa” to prose and scientific works, has been analyzed and researched. Many books and articles reveal the artistic aspects and subtleties of Alisher Navoi’s works. All this shows how deeply the authors know the works of the great poet, their artistic aspects and subtleties. Navoi’s “Khamsa” is a holistic work of five epics, which are inextricably linked. The great poet sought to write in it all the current problems and issues of his time. At the same time, he included some events in his life, sometimes knowingly and sometimes unknowingly, in the content of his works.